Pengaruh Perputaran Kas, Perputaran Piutang Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - Imran Dasena; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to knowing impact of cash turnover, receivable along with inventory on profitability in manufacturing companies listed on the ISE for the year 2015-2019. Profitability calculation uses ROA. This kind of research is quantitative, wear secondary data taken using the documentation method on the website www.idx.co.id. The type of sampling using purposive sampling, with a sample of 24 companies. Partially, cash turnover has no significant effect on profitability. This happened because of uncollectible receivables and a conservative limit on the average cash value of current assets of more than 30%. Receivable turnover has a significant effect on profitability. This happens because the company does not focus on increasing profits, but balances current liabilities. Inventory Turnover has a significant effect on profitability. This happens because inventory are provided in sufficient quantities. Simultaneously gives the result has a significant effect on profitability. This shows that working capital is carried out productively.